COMPARISON OF DIRECT AND INDIRECT SUPPLIER ACTIVITIES IN THE AUTOMOTIVE INDUSTRY FROM THE PERSPECTIVE OF A SMALL AND MEDIUM-SIZED ENTERPRISE IN KOMÁROM-ESZTERGOM COUNTY - Peredy, Zoltán; Vörös, Mihály; Péli, László (Studia Mundi – Economica, 2022)
Due to the negative impacts of the COVID-19 epidemic on the long, complex globalised multi-stage supply chains (SC) in the automotive industry, the shortening of these SC put into highlight. Supply chains closer to local manufacturers are less vulnerable to negative global processes, and issues related to knowledge and technology transfer and intellectual property rights can be better managed in the framework of cross-border cooperation. It is essential to choose the most suitable suppliers. This requires continuous monitoring of products and services, and knowledge of the requirements and performance of suppliers, as well as continuous contact with suppliers. Domestic companies that have previously proven themselves in their area of operation can become suppliers. These companies have to meet the following requirements: manufacturing technologies for products required by their direct customers and the necessary capacities operating them, adequate capital strength and company size, multilingual communication; R&D potential, ability financing the market entry costs (machinery and other investments, corporate governance systems). This case study analyses direct and indirect automotive supplier activities, showing local small and medium-sized enterprises (SMEs) the potential of indirect supply in Komárom-Esztergom county is a successful indirect supplier company through the example of Insol Kft..In general, it is easier for domestic SMEs to get into a new project than to get position in an existing, qualified supplier for direct “batch” deliveries (where parts are incorporated into the final product). On the other hand, it is easy to fall out of the circle of direct suppliers: quite a few quality defective deliveries, not the cost-effective solution or delay of deadlines as expected. Therefore, integration into the supply chain of a multinational company as an indirect supplier (which provides machines, parts, services to operate production) can be more realistic goal for them than direct supplier position. If a local SME succeeds as an indirect supplier, it can enter other European factories based on the recommendation (reference) of the given OEM or TIER1 or TIER2 and pave the way for it to become an internationalised large company.